The longitudinal change of extracellular antioxidant status during pregnancy using an electron spin resonance method. (16th September 2016) - Furukawa, Seishi; Nakajima, Akira; Sameshima, Hiroshi
Abstract: Objective : To evaluate the longitudinal change of extracellular antioxidant status during pregnancy. Methods : A longitudinal study involving 21 cases of pregnant women without medical disorders and had a vaginal birth was undertaken. Blood was obtained at early, mid and late pregnancy, labor onset, and postpartum day 1 and 5. We measured oxygen radical absorbance capacity (ORAC) and superoxide radical-eliminating ability (SREA) in serum using an electron spin resonance method. Twelve healthy volunteers were recruited as controls. Longitudinal and temporal changes were compared. Results : ORAC increased significantly during the antepartum period (at early, mid and late pregnancy), decreased once during the peripartum period (in labor and day 1), and then recovered at day 5. SREA showed a similar tendency as ORAC. Interestingly, the ORAC of controls (919.7 ± 48.2 µmol TE/L) was significantly higher than those pregnant women at early pregnancy (early pregnancy: 699.2 ± 127.5, p < 0.01) and day 1 (740.3 ± 101.0, p < 0.01). The ORAC of controls was comparable to at late pregnancy and day 5 (1066.4 ± 189.6 and 920.3 ± 106.6, respectively). The SREA of controls (77.8 ± 31.2 arbitrary unit) was high, but there was no significant difference against the study group. Conclusion : Antioxidant ability of serum clearly fluctuated during periods that may be critical, namely, early pregnancy and peripartum period.